Analisis Pengaruh Ukuran Perusahaan, Leverage, dan Profitabilitas terhadap Nilai Perusahaan (Studi pada Perusahaan Food and Beverage yang Listing di BEI tahun 2010-2013) - Priyastuty, Harning (Jurnal Ilmiah Mahasiswa FEB, 2016)
The study aims at examining the effect on firm size, leverage, and profitability as well on firm value of the Food and Beverages companies listed in Indonesia Stock Exchange. This research described the influence of three independent variables namely firm size, leverage, and profitability on firm value. This research was explanatory research. It was included in the type of quantitative research. This research used 12 firms, period of 4 years from 2010- 2013. Multiple regressions was used to analyze the data. The result showed that there was a positive relationship between profitability and firm value. It meant that as the profitability increases it will lead to increase firm value. Firm size and leverage did not affect on firm value because investor preferred to look at the other good news like CSR (Corporate Social Responsibility) and looked at firm’s ability to gain its earning than how much firm used debt. Therefore, the companies should look at the profitability and make serious effort to increase profitability, because profitability is proved to influence firm value. Keyword: Firm Size, Leverage, Profitability, Firm Value.